Capital Rationing and Organizational Slack in Capital Budgeting - Antle, Rick; Eppen, Gary D. (Management Science, 1985)
This paper reconciles three stylized facts about capital budgeting in firms and shows that they are tied to the presence of asymmetric information among the several members of the firm, each with his or her own objectives and decisions. The facts of interest are: 1. The existence of organizational slack. 2. The “rationing” of resources within organizations. 3. The stated “cut off rate” for accepting capital projects in firms is often greater than the market rate of interest. Organizational slack is defined as the excess of resources allocated over the minimum necessary to accomplish the tasks assigned. Resource rationing is defined as the under-allocation of resources; i.e., an increase in the amount allocated would generate revenues in excess of its costs. Rationing and slack are both manifestations of ex post inefficiencies. An LP model is used to show that these inefficiencies can occur in ex ante efficient organizational designs when asymmetric information is present. The optimal allocation policy involves a hurdle rate criterion in which the hurdle rate is strictly in excess of the cost of capital, thus inducing rationing in some states of the world. Typically, resources are optimally allocated such that slack exists in other states. The optimal allocation policy trades off these two inefficiencies.